Sour cherry seed as an industrial gamma tocopherol source - Bíró, Attila; Nemes, Andrea; Remenyik, Judit (Acta Agraria Debreceniensis, 2015)
In our experiments sour cherry kernels were investigated. The kernels of different sour cherry cultivars were originated from Újfehértói Gyümölcstermesztési Kutató és Szaktanácsadó Nonprofit Közhasznú Kft. Tocopherol profile, oil yields and nutritional value were stood in focus of examinations.We started processes preparing of sour cherry kernels. After the preparation recovered non-polar fraction was investigated. We worked with formerly developed chromathographic system, which is capable to separate different tocopherol isomers efficiently. We measured concentration of each tocopherol isomers and registered those and their relation in different oil samples.According to received data, alpha-, gamma- and delta-tocopherol appeared in samples, but beta-tocopherol could not be detected. It became clear that level of gamma-tocopherol is far higher than alfa- or gamma-isomer, it is concentration exceeded 1–1.5 mg ml-1.